Non-vehicle commuting in Italy: need for ergonomic action for women's lower limbs?. (February 2020) - Salerno, Silvana; Giliberti, Claudia
Abstract: Introduction: The aim of this paper is to examine gender differences in the occurrence of accidents among workers while walking to or from their workplace ( non-vehicle commuting accidents ). We have previously found that the lower limb is more often injured at work among women, compared to men, so the paper concentrates on lower limb injuries. Methods: Using the records of the National Institute for Insurance against Injuries at Work (INAIL), we focused on the non-vehicle commuting accidents of women and men recognized as work-related for the period 2013-2017. In particular, we examined the gender difference by work sector and type of trauma suffered with particular attention to lower limb injuries. Results: The rate of non-vehicle commuting accidents (n. 60, 936) among women was significantly higher than for men (1.29‰ vs 0.40‰ men, p < 0.001) for the period studied. Lower limb injuries (50.5% for women and 43.7% for men, p < 0.001) constituted the large majority of these injuries. In particular, dislocation of the ankle (78% for women vs 65.5% for men, p < 0.001), bruise of the knee (71.2% for women vs 54.9% for men, p < 0.001) and fracture of the foot (41% for women vs 33.6% for men, p < 0.001) were all significantly higher among women. The work sectors with higher injury rates were: Transport and Warehouse, Public Administration, Health and care services and Wholesale and retail trade. This result may be due to wear and tear from conditions at work. The women injured were on the average, a decade older than men (50-59 vs 40-49 years old). Conclusions: Non-vehicle commuting represents an important, albeight neglected, preventable risk for women workers, causing lower limb trauma particularly at the ankle, the foot and the knee. These areas may be particularly injure-prone among women in specific sectors, due to the work environment. Effective prevention of these injuries requires gender-oriented ergonomic actions at work and in the commuting environment. Highlights: Women have significantly more lower leg injuries during non-vehicle commuting. Dislocation of ankle, bruise of knee, fracture of foot are the prevalent lesions. Main work sectors are: Healthcare, Public administration, Retail trade, Post service. Variation of lower limb injuries in commuting may be due to conditions at work. Effective prevention requires gender oriented ergonomic actions.